Long-Term Stability of Bacterial Associations in a Microcosm of Ostreococcus tauri (Chlorophyta, Mamiellophyceae) - Vacant, Sophie; Benites, L. Felipe; Salmeron, Christophe; Intertaglia, Laurent; Norest, Manon; Cadoudal, Adrien; Sanchez, Frederic; Caceres, Carlos; Piganeau, Gwenael (Frontiers in Plant Science, 2022)
Phytoplankton–bacteria interactions rule over carbon fixation in the sunlit ocean, yet only a handful of phytoplanktonic–bacteria interactions have been experimentally characterized. In this study, we investigated the effect of three bacterial strains isolated from a long-term microcosm experiment with one Ostreococcus strain (Chlorophyta, Mamiellophyceae). We provided evidence that two Roseovarius strains (Alphaproteobacteria) had a beneficial effect on the long-term survival of the microalgae whereas one Winogradskyella strain (Flavobacteriia) led to the collapse of the microalga culture. Co-cultivation of the beneficial and the antagonistic strains also led to the loss of the microalga cells. Metagenomic analysis of the microcosm is consistent with vitamin B12 synthesis by the Roseovarius strains and unveiled two additional species affiliated to Balneola (Balneolia) and Muricauda (Flavobacteriia), which represent less than 4% of the reads, whereas Roseovarius and Winogradskyella recruit 57 and 39% of the reads, respectively. These results suggest that the low-frequency bacterial species may antagonize the algicidal effect of Winogradskyella in the microbiome of Ostreococcus tauri and thus stabilize the microalga persistence in the microcosm. Altogether, these results open novel perspectives into long-term stability of phytoplankton cultures.